2016
DOI: 10.5569/2340-5104.04.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Estigmatización, invisibilización y cosificación de las personas con diversidad funcional. Una aproximación desde la justicia como reconocimiento de Axel Honneth

Abstract: 1. Este trabajo se inscribe en el marco de la tesis doctoral presentada recientemente por el autor en la Universidad de Murcia, titulada "Trato justo con las personas con diversidad funcional. Reconocimiento e identidad, distribución, inclusión social". ResumenAxel Honneth propone, inspirándose en el joven Hegel, una concepción de la justicia basada en la idea de reconocimiento. Dicha concepción parte del previo acercamiento a una serie de fenómenos negativos, los cuales define como fallas en el reconocimient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Arrieta (2017) noted that the articulation of this phenomenon is based on achieving a balance between the social recognition of the difference without losing the common identity of the idea of dignity, which is intrinsic to all human beings. Some authors, such as Aparicio (2016), have suggested that the administrative process required to alter disability swiftly from a private to a public matter risks treating and seeing PWD as objects defined by classifications, labels, types, degrees, and levels that allow them to access different types of goods and services. Contrary to the optimistic approach of our informants on the classification of disability in Bolivia, some social analysts, such as Barroso (2018), have warned against the negative sociopsychological consequences of such classifications on the collective.…”
Section: Discussionmentioning
confidence: 99%
“…Arrieta (2017) noted that the articulation of this phenomenon is based on achieving a balance between the social recognition of the difference without losing the common identity of the idea of dignity, which is intrinsic to all human beings. Some authors, such as Aparicio (2016), have suggested that the administrative process required to alter disability swiftly from a private to a public matter risks treating and seeing PWD as objects defined by classifications, labels, types, degrees, and levels that allow them to access different types of goods and services. Contrary to the optimistic approach of our informants on the classification of disability in Bolivia, some social analysts, such as Barroso (2018), have warned against the negative sociopsychological consequences of such classifications on the collective.…”
Section: Discussionmentioning
confidence: 99%
“…Hay así reminiscencias de prescindencia en la valoración del aborto eugenésico, en la invisibilización social o en la falta de consideración del colectivo a la hora de diseñar el acceso universal y los programas de atención. Sobre todo, esto sucede a la hora de confeccionar leyes y normativas que les conciernen directamente y que afectan a su calidad de vida (Aparicio, 2016;Honneth, 2010).…”
Section: Praxis Actualunclassified
“…Según diferentes autores, la actividad laboral conjunta entre personas con discapacidad y sin discapacidad estimula la integración social de aquellos que presentan discapacidad, mejorando su desempeño en el trabajo (Vidal & Claver, 2004;Pättiniemi, 2004) Nuevamente, algunos autores indican que las empresas sociales generan beneficios terapéuticos, incluyendo una menor demanda de los servicios de salud mental, la reducción del aislamiento social y el incremento tanto de la autoestima como de la motivación por parte de la PCD (Mascayano Tapia, Lips…”
Section: A2 Integración Laboral En Empresas Socialesunclassified